Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

RICHARDSON, JOHN - Greenwood, F. Murray (Dictionnaire biographique du Canada, 1987)

GRAY, JOHN - Miller, Carman (Dictionnaire biographique du Canada, 1987)

SUTHERLAND, DANIEL - Momryk, Myron (Dictionnaire biographique du Canada, 1987)

La bourse de Montréal sous le régime français - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1915)